Digital Transformation as a Driver of Innovative Behavior: the Mediating Roles of HR Analytics and Psychological Well-being at the Library and Archives Office of Bantul Regency - Regina Devianti; Didik Subiyanto; Tri Ratna Purnamarini (SMARTINDO, 2025)
Purpose - This study aims to examine the influence of digital transformation as a driver of innovative behavior, with HR analytics and psychological well-being serving as mediating variables within the Bantul Regency Library and Archives Office. The study involved all 48 employees aged 20–50 years through direct questionnaire distribution. Data analysis was conducted using AMOS version 22 with Structural Equation Modeling (SEM), including outer model testing (validity and reliability), inner model testing (goodness-of-fit indices), and hypothesis testing. The findings indicate that digital transformation significantly influences both HR analytics and psychological well-being but does not directly affect innovative behavior. HR analytics shows no significant relationship with innovative behavior and does not mediate the effect of digital transformation. Psychological well-being, however, has a significant and positive impact on innovative behavior and serves as a partial mediator in the relationship between digital transformation and innovation. These results suggest that while technological advancement is important, its effectiveness in promoting innovation is enhanced when employee psychological well-being is also supported. This highlights the need for public institutions to integrate digital transformation strategies with initiatives that foster employee well-being, thereby cultivating a work environment that encourages innovation. Design/methodology/approach - This research uses a quantitative approach with a survey method. The population consists of all employees at the Library and Archives Office in Bantul Regency, and the study employed a saturated sampling technique, where the entire population was used as the research sample. Data were collected using Likert-scale questionnaires and analyzed using Structural Equation Modeling (SEM) with AMOS software. Validity and reliability tests were conducted to ensure the quality of the instrument, and the mediation effects were examined through bootstrapping procedures. Originality - This study provides novel insights into how digital transformation, often discussed in private sector contexts, operates in a local public government institution. It extends the literature by testing the dual mediating roles of HR analytics and psychological well-being, offering a more holistic view of innovation enablement in bureaucratic settings. Findings and Discussion - The study examined seven hypotheses to understand how digital transformation influences innovative behavior through HR analytics and psychological well-being. The results revealed that digital transformation significantly improves HR analytics and psychological well-being, but does not directly affect innovative behavior. HR analytics was not found to have a significant effect on innovative behavior, nor did it mediate the relationship between digital transformation and innovation. In contrast, psychological well-being showed a strong positive influence on innovative behavior and partially mediated the impact of digital transformation, highlighting its critical role. These findings suggest that while digital tools are essential for operational enhancement, it is the psychological state of employees that ultimately drives innovation within public institutions. Conclusion - This study concludes that digital transformation in public institutions does not directly promote innovative behavior but exerts its influence through the psychological well-being of employees. While HR analytics reflects a technological advancement in human resource management, it does not significantly contribute to fostering innovation in the observed context. In contrast, psychological well-being emerges as a key mediating factor, enabling civil servants to engage more confidently in innovative actions. These findings underscore the importance of integrating employee-centered strategies particularly those enhancing mental and emotional resilience into digital transformation initiatives. For public sector innovation to thrive, digital tools must be complemented by supportive work environments that nurture psychological health and motivation.